Right ventricular recovery during follow‐up is associated with improved survival in patients with chronic heart failure with reduced ejection fraction. (20th September 2016) - Dini, Frank Lloyd; Carluccio, Erberto; Simioniuc, Anca; Biagioli, Paolo; Reboldi, Gianpaolo; Galeotti, Gian Giacomo; Raineri, Claudia; Gargani, Luna; Scelsi, Laura; Mandoli, Giulia Elena; Cannito, Antonia; Rossi, Andrea; et al.
Abstract: Aims: A compromised tricuspid annular plane systolic excursion (TAPSE) is associated with worse survival in patients with chronic heart failure with reduced ejection fraction (HFrEF). However, it is not known whether a reversible abnormal TAPSE at follow‐up predicts survival. Our aim was to evaluate whether a reversible abnormal TAPSE is associated with a better survival in patients with chronic HFrEF. Methods and results: A complete echocardiography was performed in 706 patients with chronic HFrEF (LVEF ≤45%) at baseline and after 6 ± 3 months. Right ventricular (RV) systolic function was evaluated using TAPSE. The study endpoint was all‐cause mortality. At baseline, TAPSE was severely reduced (≤14 mm) in 89 (13%) patients, and slightly reduced (>14 but <18 mm) in 157 (22%) patients. During a median follow‐up of 40 months, 152 patients reached the endpoint. The event rate (per 100 patients/year) was lower in patients with persistently normal TAPSE (≥18 mm, n = 393) [3.3%, 95% confidence interval (CI) 2.5–4.3], and in those with reversible TAPSE ( n = 120) (4.6%, 95% CI 3.1–7.0), compared with patients with worsening TAPSE ( n = 90) (11.9%, 95% CI 8.7–16.3), and those with persistently reduced TAPSE ( n = 103) (12.6%, 95% CI 9.3–17.1; log‐rank 69.4, P < 0.0001). A reversible abnormal TAPSE was associated with improved survival at multivariable Cox regression analysis (hazard ratio 0.48, 95% CI 0.29–0.79, P = 0.004). Conclusions: Patients with chronic HFrEF who have abnormal TAPSE at baseline but reverse their dysfunction during follow‐up have better survival than patients with either worsened TAPSE or persistently abnormal TAPSE, and similar to that of patients with persistently normal TAPSE.